Social Isolation and Well-Being among Community Dwelling Elderly - Samar Abbas; Aaqib Shahzad Alvi; Maliha Gull Tarar (Journal of Management Practices, Humanities and Social Sciences, 2021)
The purpose of this cross-sectional study was to examine a link between social isolation and elderly well-being among elderly. It also probes into the nature and extent of respondents' social isolation as well as their well-being. The sample size was 150, and a multi-stage sampling procedure was employed. Data was collected using an interview schedule, a social isolation scale, and a wellbeing scale. The study's major premise was that there would be a strong link between social isolation and elderly well-being. The findings regarding the prevalenceof social isolation revealed that half of the respondents were at risk of social isolation. Sixty-six percent of the elderly reported a high degree of Wellbeing, 29 percent estimated moderate level of Wellbeing, and the remaining had a low level of Wellbeing. According to the Pearson correlation, social isolation and elderly well-being have a negative significant relationship. It means that being more likely to be socially isolated will lead to a decrease in wellbeing and vice versa.The T test results show that there was no significant difference in social isolation between men and women. On the other hand, there was a considerable difference existed in social isolation between nuclear and joint family structures. Participants in nuclear family structureexperienced higher social isolation than those in joint family structures. Various intervention measures, including as public awareness campaign, the creation of senior citizen pools, and the building of community centres, should be used to prevent social isolation and improve the social adjustment of the elderly in later life.